Facile synthesis and luminescence studies of nanocrystalline red emitting Cr:ZnAl2O4 phosphor. (February 2017) - Menon, Samvit G.; Hebbar, Deepak N.; Kulkarni, Suresh D.; Choudhari, K.S.; Santhosh, C.
Graphical abstract: Highlights: Red emitting Cr:ZnAl2 O4 phosphor synthesized by co-precipitation for first time. Annealing increased transparency & material colour changed from green to pink. PL spectra comprised of zero phonon R line (688 nm) & multi phonon side bands. Excitation spectra revealed asymmetric band at 400 nm owing to trigonal distortion. High Dq/B suggested PL could be associated with spin-parity forbidden transitions. Abstract: A simple co-precipitation synthesis of Cr:ZnAl2 O4 nanoparticles is reported for the first time. The materials were characterized by XRD, FE-SEM, HR-TEM, FT-IR, Diffuse reflectance and Photoluminescence spectroscopy. Annealing increased the transparency and material colour changed from green (500 °C) to pink (1200 °C) owing to the diffusion of Cr 3+ into the ZnAl2 O4 matrix. The intensity of two broad bands (540 nm, 400 nm) in the excitation spectra increased with annealing temperature. The asymmetric band at 400 nm comprised of two bands attributed to the trigonal distortion. Cr 3+ emissions obtained, comprised of a zero phonon line (R line) and multi phonon side bands on either side. Higher Dq/B (2.96), confirmed Cr 3+ ions in a strong crystal field and thus the photoluminescence emission could be associated with spin-parity forbidden transitions. Photoluminescence lifetimes ranged from 20 to 30 ms for samples annealed at higher temperatures. The reported work can be extended to other phosphors for bioimaging, waveguides and sensors.